Impact of Accounting Knowledge, Use of Accounting Information, and Financial Inclusion on Business Growth: A Case Study at BRI Pagesangan - Ema Kusumawati; Animah , Animah (Tinta Emas Institute, 2024)
In the current era of globalization, trade is essential for a country to boost its economy, including both micro and macro trade. The development of MSMEs requires MSME actors to be ready to compete with other businesses. This pushes MSME entrepreneurs to continuously innovate by creating unique, superior products; in addition, MSMEs are expected to have sound financial management. This study employs an associative research method with multiple linear regression to examine the relationship between accounting knowledge, accounting information utilization, and financial inclusion on the business development of Bank BRI KCP Pagesangan Unit clients. Based on multiple linear regression analysis results, it is concluded that accounting knowledge, accounting information utilization, and financial inclusion significantly influence business development. Accounting knowledge has been shown to have a positive and significant effect on business development, while accounting information utilization also plays an important role in supporting business development. Additionally, financial inclusion has a significant impact on client business development. Based on these findings, it is recommended that Bank BRI KCP Pagesangan Unit prioritize training and outreach programs on accounting knowledge, accounting information utilization, and the importance of financial inclusion for their clients. By enhancing clients' understanding and skills in accounting, they can more effectively manage their finances and make better business decisions.